Bats Oxidative Stress Defense - Desrayni Hanadhita; Aryani Sismin Satyaningtijas; Srihadi Agungpriyono (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Antioxidants and free radicals have long been known to be the main factors in the occurrence of degenerative diseases. Various studies related to antioxidants and free radicals which have implications for oxidative stress have increased in the last decade. Knowledge of stress oxidative physiology in various animals help in understanding the pathophysiology of diseases associated with oxidative stress. Bats are claimed to be the best known animals in term of survival compared to other mammals. Bats are reported to produce low reactive oxygen species (ROS) but high endogenous antioxidants that can prevent oxidative stress. Bats high defense against oxidative stress has implications for their extreme longevity, the role as a reservoir of viruses, and the potential as experimental animals.